2022
DOI: 10.1093/ibd/izac177
|View full text |Cite
|
Sign up to set email alerts
|

Fusobacterium nucleatum Extracellular Vesicles Promote Experimental Colitis by Modulating Autophagy via the miR-574-5p/CARD3 Axis

Abstract: Background Ulcerative colitis (UC) may be exacerbated by Fusobacterium nucleatum (Fn) infection. However, the mechanism underlying Fn-mediated progression of UC has yet to be established. Here, we aimed to establish whether and how Fn-derived extracellular vesicles (Fn-EVs) participate in the development of experimental colitis through microRNAs (miRNAs). Methods EVs were isolated and purified by ultracentrifugation from Fn a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“… 136 MVs from Fn promoted the secretion of proinflammatory cytokines IL-8 and TNF-α in vitro in colonic epithelial cells. 27 Fn -MVs triggered an upregulation of the proinflammatory cytokines IL-1β, IL-6, TNF-α, and iNOS 28 , 134 and downregulation of anti-inflammatory IL-10 in vitro in intestinal epithelial cells and in vivo in colitis mice. 134 Increased levels of F4/80+ iNOS+M1-like macrophages were also reported; thus, Fn -MVs enhanced apoptosis of intestinal epithelial cells in vivo by inducing the pro-inflammatory M1 phenotype resulting in intestinal barrier dysfunction in UC ( Figure 6 ).…”
Section: Mvs and Their Potential Role In Ibdmentioning
confidence: 94%
See 4 more Smart Citations
“… 136 MVs from Fn promoted the secretion of proinflammatory cytokines IL-8 and TNF-α in vitro in colonic epithelial cells. 27 Fn -MVs triggered an upregulation of the proinflammatory cytokines IL-1β, IL-6, TNF-α, and iNOS 28 , 134 and downregulation of anti-inflammatory IL-10 in vitro in intestinal epithelial cells and in vivo in colitis mice. 134 Increased levels of F4/80+ iNOS+M1-like macrophages were also reported; thus, Fn -MVs enhanced apoptosis of intestinal epithelial cells in vivo by inducing the pro-inflammatory M1 phenotype resulting in intestinal barrier dysfunction in UC ( Figure 6 ).…”
Section: Mvs and Their Potential Role In Ibdmentioning
confidence: 94%
“… 28 Another study reported that Fn -derived MVs downregulated tight junction proteins ZO-1 and occludin, resulting in epithelial barrier dysfunction both in vitro and in vivo . The exacerbation of colitis by the MVs was linked with Fn -MVs facilitated downregulation of miR-574-5p expression and activation of autophagy 134 ( Figure 6 ).
Figure 6.
…”
Section: Mvs and Their Potential Role In Ibdmentioning
confidence: 96%
See 3 more Smart Citations